Modeling College Graduation GPA Considering Equity in Admissions: Evidence from the University of Puerto Rico - Matos-Diaz, Horacio; Garcia, Dwight (Education Policy Analysis Archives, 2014)
Over concerns about private school students’ advantages in standardized tests, beginning in 1995–96 the University of Puerto Rico (UPR) implemented a new admissions formula that reduced the weight they previously had in the General Admissions Index (GAI), on which its admissions decisions are based. This study seeks to determine the possible effects of the new GAI regarding both its objective of promoting equity in the student body composition and as a measure of academic aptitude capable of predicting student success. With these aims, the study compares the old and new GAI averages of 11 consecutive entering cohorts at the Bayamón campus of the UPR, and models the graduation GPA (GGPA) of 6 of these cohorts. Evidence shows that (a) the new GAI eliminated private school students’ advantage over those from public schools and reduced to a minimum the gap between genders; (b) female students obtain significantly higher GGPAs and exhibit other advantages when compared to males, while public and private school students’ academic outcomes are broadly similar; (c) the probability of accessing a determined boundary in the GGPA distribution is significantly and nonlinearly related to the GAI; (d) GGPAs exhibit an uptrend that varies inversely and significantly with the GAI, and (e) the probability of being in the lower bounds of the GGPA distribution increases to the extent that graduates exceed graduation required time.